2015
DOI: 10.1242/dev.124271
|View full text |Cite
|
Sign up to set email alerts
|

Aspm sustains postnatal cerebellar neurogenesis and medulloblastoma growth

Abstract: Alterations in genes that regulate brain size may contribute to both microcephaly and brain tumor formation. Here, we report that Aspm, a gene that is mutated in familial microcephaly, regulates postnatal neurogenesis in the cerebellum and supports the growth of medulloblastoma, the most common malignant pediatric brain tumor. Cerebellar granule neuron progenitors (CGNPs) express Aspm when maintained in a proliferative state by sonic hedgehog (Shh) signaling, and Aspm is expressed in Shh-driven medulloblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 79 publications
1
71
0
Order By: Relevance
“…ATR is activated in response to stalled DNA replication forks (Nam and Cortez, 2011), which can be caused by exogenous (Harley et al, 2016;Harper et al, 2010) or endogenous (Willis et al, 2013) factors. We have previously shown that normal CGNP proliferation produces endogenous DNA damage, detectable as small γH2A.X + foci (Williams et al, 2015). We now show that ATR mitigates endogenous, proliferation-associated DNA damage in CGNPs in order to maintain replication fidelity.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…ATR is activated in response to stalled DNA replication forks (Nam and Cortez, 2011), which can be caused by exogenous (Harley et al, 2016;Harper et al, 2010) or endogenous (Willis et al, 2013) factors. We have previously shown that normal CGNP proliferation produces endogenous DNA damage, detectable as small γH2A.X + foci (Williams et al, 2015). We now show that ATR mitigates endogenous, proliferation-associated DNA damage in CGNPs in order to maintain replication fidelity.…”
Section: Discussionmentioning
confidence: 62%
“…Prior studies showed that deletion of the apoptosis gatekeeper Bax is sufficient to stabilize CGNPs with radiationinduced or proliferation-associated DNA damage (Chong et al, 2000;Garcia et al, 2013;Williams et al, 2015). We found, however, that apoptosis of Atr-deleted CGNPs and cerebellar hypoplasia were not prevented by Bax co-deletion in Math1-Cre;Atr loxP/loxP ; Bax loxP/loxP (Atr;Bax M-cre ) animals ( Fig.…”
Section: Deletion Of Bax and Bak Prevents Cell Death In Atr Mutant Cgnpsmentioning
confidence: 59%
See 3 more Smart Citations